ANALISIS HUBUNGAN LAND SURFACE TEMPERATURE (LST) DAN INDEKS KERAPATAN VEGETASI (NDVI) DAS WANGGU, SULAWESI TENGGARA - Vivi Fitriani; La Gandri; Lies Indriyani; Sahindomi Bana; La De Ahmaliun (Fakultas Pertanian, Universitas Riau, 2023)
LST and NDVI analysis in Das Wanggu utilizes Landsat 9 satellite remote sensing. LST calculations usde thermal band 10 and NDVI used Red band (Band 4) and InfraRed Band (Band 5). There are 5 LST classes, 17.25 oC -19.66 oC with an area of 908.16 Ha, 19.66 0C-22.08 oC covering 6973.71 Ha, 22.08 oC -24.49 oC covering 21748.26 Ha, 24.49 oC -26.90 oC covering an area of 4235.37 Ha, and 26.90 oC -29.31 oC with a wide coverage of 81.18 Ha, while NDVI values obtained 3 classes namely NDVI <0.2 of 1783.643 Ha, NDVI with a range of 0.2 – 0.5 covering an area of 28617.74 Ha, and areas with NDVI > 0.5 covering an area of 3544.87 Ha. The amount of LST is highly dependent on the type of land cover and land use. NDVI indicates the presence of vegetation in the study area. A negative relationship was found between LST and NDVI in Das Wanggu with a Correlation Coefficient of -0.179.